2006
DOI: 10.1002/ijc.22322
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma does not express argininosuccinate synthetase and is highly sensitive to arginine deprivationviaarginine deiminase

Abstract: Material and methods Cell cultureRenal cell carcinoma cell lines (Caki-1, Caki-2, ACHN, SN12C, SN12PM6, RENCA) were purchased from Korean Cell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 36 publications
6
102
0
1
Order By: Relevance
“…Based on this study, clinical trials in mesothelioma have been initiated [Szlosarck, personal communication]. ADI-PEG20 is also active in certain renal cell cancer cell lines which do not express ASS [16]. Interestingly, some renal cell cancers also are negative for ASS by immunohistochemical staining despite high levels of these enzymes found in the kidney.…”
Section: Antitumor Activity Of Adi-peg20 In Hepatocellular Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this study, clinical trials in mesothelioma have been initiated [Szlosarck, personal communication]. ADI-PEG20 is also active in certain renal cell cancer cell lines which do not express ASS [16]. Interestingly, some renal cell cancers also are negative for ASS by immunohistochemical staining despite high levels of these enzymes found in the kidney.…”
Section: Antitumor Activity Of Adi-peg20 In Hepatocellular Carcinomamentioning
confidence: 99%
“…Thus, depletion of this amino acid by asparaginase therapy is generally well tolerated since normal human cells do not require asparagine. Thus, eliminating a certain Several laboratories have reported that certain tumor cell lines such as melanoma, hepatocellular carcinoma, renal cell carcinoma and some mesotheliomas do not express ASS, and hence become auxotrophic for arginine [9,11,[15][16][17][18]. Consequently, arginine degrading enzyme has been shown by several laboratories to have antitumor effect in these tumors [9,13,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrulline can be recycled back to arginine in normal cells which express argininosuccinate synthetase (ASS), whereas ASS(-) tumor cells cannot. Loss of ASS expression has been most widely associated with melanoma and hepatocellular carcinoma, although it has now been identified in other tumor types including pancreatic cancer, leukemia, prostate cancer and renal cell carcinoma (Gong et al, 2000;Ensor et al, 2002;Yoon et al, 2007;Bowles et al, 2008;Kim et al, 2009).…”
Section: Enzymatic Degradation Of Argininementioning
confidence: 99%
“…Histological examination of the tumors revealed that tumor angiogenesis and vascular endothelial growth factor (VEGF) expression were significantly diminished by ADI administration (Yoon et al, 2007). Bowles et al (2008) evaluated the level of ASS expression in 47 human pancreatic adenocarcinoma specimens and 20 normal pancreas biopsies.…”
Section: Enzymatic Degradation Of Argininementioning
confidence: 99%